Experimental investigation of vortex-induced vibration of a flexible pipe in bidirectionally sheared flow. (October 2022) - Fu, Xuepeng; Fu, Shixiao; Ren, Haojie; Xie, Wenhui; Xu, Yuwang; Zhang, Mengmeng; Liu, Zhenhui; Meng, Shuai
Abstract: The existence of a bidirectionally sheared flow field caused by internal solitary waves has recently been confirmed according to a field survey in the South China Sea. A model test of a tensioned flexible pipe in bidirectionally sheared flow was performed in an ocean basin. The model was 28.41 mm in diameter and 7.64 m in length. The purpose of the model test was to understand the response performance and obtain benchmark data of vortex-induced vibration (VIV) in bidirectionally sheared flow. The test was performed on a rotating test rig to simulate bidirectionally sheared flow conditions. Fiber Bragg Grating (FBG) strain sensors were arranged along the test pipe to measure bending strains, and the modal analysis approach was used to determine the VIV response. Reduced velocities based on the tested first natural frequency in water reached 30.79. The cross-flow and in-line VIV amplitudes, response frequencies in statistics and time-domain analysis, traveling wave characteristics, phase synchronization and trajectories are presented in this article. The maximum root mean square (RMS) VIV amplitudes in the test reached 0.51 diameters and 0.18 diameters in the cross-flow and in-line directions, respectively. A relative low Strouhal number of 0.10 was found in the CF direction. Highlights: An experiment of a flexible pipe that was 28.41 mm in diameter and 269 diameters in length under bidirectionally sheared flow was conducted. The bending strain of VIV was measured in the CF and IL directions at 9 and 14 locations, respectively. A total of 58 test conditions with maximum flow velocities varying from 0.30 to 1.39 m/s were used in this experiment. The RMS VIV response in the CF and IL directions reached maximum levels of 0.51 D and 0.18 D, respectively. The '2n/n' and '2n/2n-1' modal groups, modal groups '3/1' and '4/1' existed under low flow velocity due to the special flow profile. The Strouhal numbers under the bidirectional sheared flow were approximately 0.10 and 0.24 in the CF and IL directions, respectively, which were smaller than the St numbers under uniform flow and linearly sheared flow. A strong traveling wave and 'multi-frequency' response phenomenon were found, particularly in the IL directions.